Losing Susan : brain disease, the priest's wife, and the God who gives and takes away - Austin, Victor Lee (Brazos Press, 2016)
"In this personal story of love and loss, a seasoned pastor-theologian shares how caring for his wife during her long and painful struggle with brain cancer brought him face-to-face with his God and with his faith in unsettling ways,"--NoveList.